High-resolution esophageal manometry in patients with achalasia - A. A. Smirnov; M. M. Kiriltseva; M. E. Luybchenko; L. I. Davletbaeva; A. V. Kochetkov (Вестник хирургии имени И.И. Грекова)
Introduction. At present, high-resolution esophageal manometry is the «gold standard» for the diagnosis of esophageal achalasia, based on the determination of the integrated relaxation pressure of the lower esophageal sphincter, the value of which in the case of achalasia must exceed 15 mm Hg (MMS System). However, in some patients with clinically and radiologically confirmed achalasia, this value is normal. There is no unified view of the cause of this phenomenon. We assumed that low pressure figures may be affected by incorrect installation of the manometric catheter.Methods and materials. This research included 149 patients (61 by retrospective estimating the patients data and 88 new patients) with achalasia established during the period from January 2017 to March 2020. When it was impossible to localize the lower esophageal sphincter and take correct measurements during high-resolution manometry in new patients, the X-rays or upper endoscopy was performed to control the manometric catheter placement. If its’ placement was incorrect and the integrated relaxation pressure level was lower than 15 mmHg, repeated high-resolution manometry was performed with the over-the-guidewire manometric catheter placing.Results. In 36 patients of both groups (24.2 %), the manometric data did not correspond to esophageal achalasia; in the prospective group, 12 out of the 19 patients had incorrect manometric data due to inability to visualize lower esophageal sphincter. In the prospective group, the manometric catheter was reinstalled by a guidewire, which allowed visualizing the signs of the lower esophageal sphincter in all cases, and in 15 out of 19 patients (79 %), the integrated relaxation pressure of the lower esophageal sphincter was more than 15 mm Hg.Conclusions. In some cases, the over-the-guidewire installing makes it possible to pass catheter through the lower esophageal sphincter correctly, visualize the lower esophageal sphincter during the high-resolution manometry examination and obtain true pressure values.